2021
DOI: 10.1007/s10639-021-10572-6
|View full text |Cite
|
Sign up to set email alerts
|

M-learning in the COVID-19 era: physical vs digital class

Abstract: Emerging technologies, such as the development of the Internet of Things and the transition to smart cities, and innovative handheld devices have led to big changes in many aspects of our lives, while more changes were imminent. Education is also a sector that has undergone huge changes due to the spreading of those devices. Even at the era of feature phones, it started to become clear that portable devices with access to the internet can be used for learning. The process of learning with the use of mobile pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 71 publications
0
42
0
6
Order By: Relevance
“…On the other hand, it should be noted that when it comes to university staff, the app allows our personnel to follow the students beyond lectures halls and hospital wards, tracking their progress in the acquisition of capacities, and identifying potential problems in specific lectures where students show a poorer performance when answering the multiplechoice question of the app [24]. To wit, the interaction between students and teachers has been highlighted by other authors as one of the most significant parameters to take into account when designing M-Learning solutions [19,28]. Surprisingly, we have not found differences in the perceived utility of the app for improving skills and acquiring knowledge depending on the previous self-reported degree of digital competence, as other authors had previously reported [58].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it should be noted that when it comes to university staff, the app allows our personnel to follow the students beyond lectures halls and hospital wards, tracking their progress in the acquisition of capacities, and identifying potential problems in specific lectures where students show a poorer performance when answering the multiplechoice question of the app [24]. To wit, the interaction between students and teachers has been highlighted by other authors as one of the most significant parameters to take into account when designing M-Learning solutions [19,28]. Surprisingly, we have not found differences in the perceived utility of the app for improving skills and acquiring knowledge depending on the previous self-reported degree of digital competence, as other authors had previously reported [58].…”
Section: Discussionmentioning
confidence: 99%
“…The easy access of different digital platforms or web resources in distance education courses on internet-based video conferencing programs may have reduced the frequency of textbook usage. According to Matzavela and Alepis (2021), intelligent tutoring systems and social networks have had rapid growth in online courses, especially in the COVID-19 era. As a matter of fact, during the Covid -19 pandemic periods, the use of interactive digital resources has become more widespread.…”
Section: Discussionmentioning
confidence: 99%
“…While procedural learning is not based on mobile learning, it can be carried out utilizing YouTube, which is accessible via a variety of electronic devices, as well as, of course, movable ones (Lee & Lehto, 2013). Matzavela and Alepis (2021) formed a TAM-based system that was used to explore the use of portable devices by students for primary school teachers. Researchers have used the TAM model to study how users in various sectors accept and embrace technology.…”
Section: Theoretical Foundationmentioning
confidence: 99%